One-pot synthesis of clay-dispersed poly(styrene-co-acrylonitrile) copolymer nanocomposite using poly(epsilon-caprolactone) as a compatibilizer - Ko, MB (POLYMER SOC KOREA, 2000)
Clay-dispersed nanocomposites have been prepared by simple melt-mixing of three components, i.e. poly (styrene-co-acrylonitrile) copolymer (SAN), poly(epsilon-caprolactone) (PCL), and an organophilic clay (Cloisite(x) 30A). In the present study, poly(epsilon-caprolactone) was added in the mixtures in order to facilitate the intercalation of SAN into the gallery of silicate layers, and the molecular weight effects of PCL on the dispersion of silicate layers were compared by changing the amount of added PCL. The degree of dispersion of 10-Angstrom-thick silicate layers of clay in the nanocomposites was investigated by using an X-ray diffractometer and a transmission electron microscope. It was found that PCL added in the mixture facilitate the intercalation of SAN copolymers into the galleries of silicate layers modified with an organic intercalant, resulting in the better dispersion of clay. It was, also, observed that the processing temperature influences the degree of clay dispersion.